A Systematic Review of Naltrexone for Attenuating Alcohol Consumption in Women with Alcohol Use Disorders. (3rd February 2017) - Canidate, Shantrel S.; Carnaby, Giselle D.; Cook, Christa L.; Cook, Robert L.
Abstract : Several clinical trials have evaluated naltrexone as a treatment for alcohol use disorders (AUDs), but few have focused on women. The aim of this review was to systematically review and summarize the evidence regarding the impact of naltrexone compared to placebo for attenuating alcohol consumption in women with an AUD. A systematic review was conducted using PubMed, Cochrane, Web of Science, CINAHL, and Alcohol Studies Database to identify relevant peer‐reviewed randomized controlled trials (RCTs) published between January 1990 and August 2016. Seven published trials have evaluated the impact of naltrexone on drinking outcomes in women distinct from men; 903 alcohol‐dependent or heavy drinking women were randomized to receive once daily oral or depot (injectable) naltrexone or placebo with/without behavioral intervention. Two studies examining the quantity of drinks per day observed trends toward reduction in drinking quantity among women who received naltrexone versus placebo. The 4 studies examining the frequency of drinking had mixed results, with 1 study showing a trend that favored naltrexone, 2 showing a trend that favored placebo, and 1 that showed no difference. Two of the 3 studies examining time to relapse observed trends that tended to favor naltrexone for time to any drinking and time to heavy drinking among women who received naltrexone versus placebo. While the growing body of evidence suggests a variety of approaches to treat AUD, the impact of naltrexone to combat AUD in women is understudied. Taken together, the results suggest that naltrexone may lead to modest reductions in quantity of drinking and time to relapse, but not on the frequency of drinking in women. Future research should incorporate sophisticated study designs that examine gender differences and treatment effectiveness among those diagnosed with an AUD and present data separately for men and women. Abstract : To date, seven published trials have evaluated the impact of naltrexone on drinking outcomes in women distinct from men. The existing studies suggest that naltrexone may lead to modest reductions (or no effect) in quantity of drinking and time to relapse, but the results were more inconsistent for frequency of drinking in women. Protective or harmful indicated either a p < 0.05 or a trend showing at least a 20% difference in outcomes in naltrexone versus placebo.